The Mining Industry Role in Emerging Infectious Diseases Preparedness and Response "Outside the Fence". - Ana Llamas; Emmeline Buckley; Francesca Viliani; Michael Edelstein; Osman Dar (Open Journal of Tropical Medicine - Peertechz Publications, 2017)
Introduction: Emerging Infectious Diseases (EIDs) such as Ebola are a significant threat to global health. It is unclear whether the mining industry has adequately considered EID risks, and more generally the challenge of communicable diseases. The objective of this project was to explore the acceptability of measures to assess and mitigate the risk of EIDs in the mining industry. Methodology: The study followed a qualitative methodology. Using purposive and snowball sampling,18 telephone interviews were completed, in four international mining companies based in the Democratic Republic of Congo. Data were analysed thematically and comparatively; interview results were triangulated with findings from a field visit conducted by the research team. Results: Mining companies had adequate infection prevention and control measures (IPC) "inside the fence" but were vulnerable to disease outbreaks "outside the fence", in the surrounding communities. To reduce their exposure to disease outbreaks and thus productivity loss, mining companies implemented health programmes in the surrounding communities and supported them when an outbreak took place. This included capacity building, providing resources, and sharing epidemiological intelligence and public health advice. The main barriers for further collaboration between mining companies and local health systems identified related to financial and feasibility issues, as well as the poor infrastructure and state of the health system. Conclusions: The potential contribution of the industry to EID preparedness and response has not yet been maximised. Collaboration between mining companies and other stakeholders (e.g. NGOs and the public sector) could help prevent and control future outbreaks in a coordinated, economical manner and thus reduce loss of productivity and, most importantly, loss of lives.